The effect of work-life balance and work satisfaction on work productivity of employees of the Special Capital Region of Jakarta - Mutia Garini Rahajeng; Kristin Handayani (Jurnal Ekonomi Perusahaan, 2022)
There are thousands of studies that study the factors that affect work productivity. Most studies take private companies as the research context. In this study, the researchers conducted a study on government employees who are generally considered to have lower productivity than the private sector. The question is, does this assumption apply to local governments that provide high welfare to their employees? To answer this question, the researchers deliberately selected as many as 144 local government employees specifically for the capital city of Jakarta. Data were collected using a questionnaire distributed through electronic media. The dependent variable is work productivity, and the independent variable is work-life balance and job satisfaction. SEM analysis using SmartPLS 3.0 shows that work-life balance has no direct effect on work productivity. The effect of work-life balance on work productivity occurs through job satisfaction. In this relationship, job satisfaction plays a full mediation role. Original Article | Turnitin